2022
DOI: 10.1186/s12885-021-09125-4
|View full text |Cite
|
Sign up to set email alerts
|

Ceftazidime and cefepime antagonize 5-fluorouracil’s effect in colon cancer cells

Abstract: Background Drug-drug interaction (DDI), which can occur at the pharmacokinetics and/or the pharmacodynamics (PD) levels, can increase or decrease the therapeutic or adverse response of a drug itself or a combination of drugs. Cancer patients often receive, along their antineoplastic agents, antibiotics such as ß-lactams to treat or prevent infection. Despite the narrow therapeutic indices of antibiotics and antineoplastic agents, data about their potential interaction are insufficient. 5-fluoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…It is also a beneficial drug in the case of certain wound infections and food poisoning. The anticancer activity of ceftazidime, in which it inhibits DLD-1 cells by inducing apoptotic cell death, was also reported very recently [15]. When ceftazidime given to the patients in the form of an injection given intravenously or intramuscularly, therefore, its interaction with HSA inside human body is highly anticipated.…”
Section: Introductionmentioning
confidence: 76%
“…It is also a beneficial drug in the case of certain wound infections and food poisoning. The anticancer activity of ceftazidime, in which it inhibits DLD-1 cells by inducing apoptotic cell death, was also reported very recently [15]. When ceftazidime given to the patients in the form of an injection given intravenously or intramuscularly, therefore, its interaction with HSA inside human body is highly anticipated.…”
Section: Introductionmentioning
confidence: 76%
“…Also according to cell cycle analysis as showing the percentage of cells in the different phases of the cell cycle (pre-G1, G0/G1, S, and G2/M) phases, it was detected that by affecting the cell cycle, cefepime slowed down the rate of cell division and caused the cells to arrest in the S and G2/M phases. Pfab et al (2022) showed that the cefepime alone increased slightly the cells in pre-G1 in HCT-116 cells up to 72 h post-treatment. The IC50 values and cytotoxic effects of pharmacological agents may change depending on the cell line used, the method of administration and the laboratory condition (Cortes et al, 2001).…”
Section: Discussionmentioning
confidence: 95%
“…Most importantly, drugs such as ceftazidime (CFT) and cefepime (CFP) have been shown to interfere with the action of 5‐FU. [ 19 ] As a result, it is critical to investigate 5‐FU derivatives to overcome the aforementioned issues.…”
Section: Introductionmentioning
confidence: 99%